If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+25)+(2x+18)=(x2+3)
We move all terms to the left:
(x+25)+(2x+18)-((x2+3))=0
We add all the numbers together, and all the variables
-((+x^2+3))+(x+25)+(2x+18)=0
We get rid of parentheses
-((+x^2+3))+x+2x+25+18=0
We calculate terms in parentheses: -((+x^2+3)), so:We add all the numbers together, and all the variables
(+x^2+3)
We get rid of parentheses
x^2+3
Back to the equation:
-(x^2+3)
3x-(x^2+3)+43=0
We get rid of parentheses
-x^2+3x-3+43=0
We add all the numbers together, and all the variables
-1x^2+3x+40=0
a = -1; b = 3; c = +40;
Δ = b2-4ac
Δ = 32-4·(-1)·40
Δ = 169
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{169}=13$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-13}{2*-1}=\frac{-16}{-2} =+8 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+13}{2*-1}=\frac{10}{-2} =-5 $
| 2.6y-6+0.1y=9 | | 3.5(n+5)−8=22 | | 1/4(7x-16)=3 | | x=6+3/8 | | x-6÷3=6 | | 4y-4+2(4y+1)=4(y+4) | | -2(7b+8)=8-8b | | -5x-7(-7-4x)=2(3x-4) | | 4(2x-6)=27 | | 4.6-4x=-22 | | g=4+0.93/3 | | 4(w+8)=7+4w | | -4(u-8)=-6u+22 | | 16.57=3g+3.64 | | 31-2(6x-50)=47 | | 6(x-7=10(x+4) | | 3(x-16)=56 | | b(b-3)=10 | | 2(4x)+2(3x+2)=116 | | 8x-(2x+8)=8x-20 | | 8x+11+14x-1=0 | | -2(8v-9)+2v=4(v+4) | | 18-4k=-10=4k | | 1/2(2x-20)=2(3x-5) | | 4(3x+7)−6(4x−7)=11x+3(4x−6) | | 12(x-2)+3x=1.2(x+6)+2 | | 11x-1=x+9 | | 55=55-11u | | 28a=-84 | | 3d-5=-2+3d | | -8y-13=14y+11 | | 7(v-1)-5=-6(-5v+4)-5v |